Fresno County Bar Association Law Day Luncheon with Keynote Speaker Justice Pauline Davis Hanson - Watkins, Howard::::::::: (1982)
Mary Ludy, Elaine Harris, Catherine Bennett, Justice Pauline Hanson ?????